Similarity and Distance Measures of Picture Fuzzy Sets with Application in Pattern Recognition (Jagannath University Journal of Science, 2024)
Picture fuzzy set is the latest influential conception to conduct ambiguous data effectively. The distance and similarity measures are two dominant concepts to calculate the characteristics between two PFSs. The similarity measure evaluates the closeness between the two PFSs where the larger similarity measure corresponds to the closer degree of two PFSs. In this article, a new similarity measure is developed considering the influence of the abstain and refusal groups as each of these influences the results. Finally, a pattern recognition application is illustrated to justify the effectiveness of this new technique and compare the results with other existing methods.Jagannath University Journal of Science, Volume 11, Number 1, June 2024, pp. 106−117